2002
DOI: 10.1029/2001ja005089
|View full text |Cite
|
Sign up to set email alerts
|

Four‐point Cluster application of magnetic field analysis tools: The discontinuity analyzer

Abstract: [1] The Cluster spacecraft have collected 3-D information on magnetic field structures at small to medium scales (100-1000 km) in the Earth's dayside magnetosphere, magnetosheath, and near solar wind. We focus here on the first application of the discontinuity analyzer analysis technique (determination of the geometry and motion of magnetic discontinuities, using interspacecraft timing and variance information) for the case of boundaries that are planar over the four-spacecraft array. This multipoint technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 21 publications
3
64
0
1
Order By: Relevance
“…This means that none of them are pure spatial structures, stationary in the geomagnetic coordinate system used here. However, the fact that there are consistent time shifts enables us to interpret the observations in intervals (1) and (3) as quasi-stationary structures moving over the satellite, similar to Cluster observations of magnetopause crossings Pedersen et al, 2001;Dunlop et al, 2002). By assuming that the structures are elongated in a plane with no variations along the plane, at least over a length comparable to the satellite separations, we can determine the angle α of the plane and its velocity component v ⊥ perpendicular both to B and to the plane itself, which best reproduces the observed time shifts.…”
Section: Cross-correlation Analysis Minimum Variance Analysismentioning
confidence: 99%
“…This means that none of them are pure spatial structures, stationary in the geomagnetic coordinate system used here. However, the fact that there are consistent time shifts enables us to interpret the observations in intervals (1) and (3) as quasi-stationary structures moving over the satellite, similar to Cluster observations of magnetopause crossings Pedersen et al, 2001;Dunlop et al, 2002). By assuming that the structures are elongated in a plane with no variations along the plane, at least over a length comparable to the satellite separations, we can determine the angle α of the plane and its velocity component v ⊥ perpendicular both to B and to the plane itself, which best reproduces the observed time shifts.…”
Section: Cross-correlation Analysis Minimum Variance Analysismentioning
confidence: 99%
“…As a quality indicator for the estimated current, the quantity |∇·B|/|∇×B| can be used. In theory, this quantity should be identically zero, but in practice it can vary substantially (Paschmann and Daly, 1998;Dunlop et al, 2002) due to, for example, small-scale variations in the magnetic field and measurement errors. It should be noted that a oneto-one correspondence between the value of |∇·B|/|∇×B| and the actual error in the estimated current density is not expected.…”
Section: Cluster Datamentioning
confidence: 99%
“…In two recent papers, Dunlop et al (2001Dunlop et al ( , 2002 have concluded from studies of Cluster magnetopause events that the magnetopause speed was usually not constant during an event but could change drastically over times of the order of a minute or less, whereas the thickness showed more modest variations. The method employed in reaching this conclusion makes use of magnetopause normal vectors obtained from minimum variance analysis of the magnetic field data taken during each of the four crossings, in addition to the timing information.…”
Section: Introductionmentioning
confidence: 99%